Purification and properties of a binding protein for branched-chain amino acids in Pseudomonas aeruginosa. - Hoshino, T (1980)
A binding protein for branched-chain amino acids was purified to a homogeneous state from shock fluid of Pseudomonas aeruginosa PML14. It was a monomeric protein with an apparent molecular weight of 4.3 x 10(4) or 4.0 x 10(4) by sodium dodecyl sulfate-polyacrylamide gel electrophoresis or gel filtration, respectively. The isoelectric point was determined to be pH 4.1 by electrofocusing. Amino acid analysis of the protein showed that aspartic acid, glutamic acid, glycine, and alanine were major components and that the protein contained only one residue each of tryptophan and cysteine per molecule. The binding protein contained no sugar. The binding activity of the protein was specific for the branched-chain amino acids. The protein also bound alanine and threonine with lower affinity. The dissociation constants of this protein for leucine, isoleucine, and valine were found to be 0.4, 0.3, and 0.5 microM, respectively. Mutants defective in the production of the binding protein were identified among the mutants deficient in a transport system for branched-chain amino acids (LIV-I). The revertants from these mutants to LIV-I-positive phenotype simultaneously recovered normal levels of the binding protein. These findings suggest strongly the association of the binding protein with the LIV-I transport system.